O sistema produtivo da mandioca e seu aproveitamento industrial no Estado da Bahia: estudo de caso nos territórios de identidade Portal do Sertão, Vitória da Conquista e Recôncavo - RIBEIRO, Joselito de Macêdo (2014)
Cassava is one of the principle foods consumed in Brazil, especially in the Northeast of the country. It is eaten with daily meals, in the form of flour and in the preparation of specific dishes in which this tuber is a fundamental ingredient, and is a prime source of energy for humans and animals. It is cultivated in almost the entire country, usually in areas inappropriate for other crops as it doesn’t require highly fertile soil and adapts well to dry climate. The objective of this study is to analyze how the production chain system for cassava and it derivative operate in Bahia. The study consists of a case study in three regions, domestics and family properties and cooperative that work with cassava, from the planting stage to the commercialization of products derived from the crop, and aims to determine if this industry has contributed to regional development. This exploratory study utilized bibliographical, documentary and field study methods. Data collection techniques included questionnaires and direct observation, together with a sample group consisting of 83 rural producers and one cooperative, selected according to either intentional probabilistic sampling technique or judgment sampling technique. It can be concluded that the cassava production chain is not capacitated or sufficiently organized to take advantage of the opportunities that the market offers. Thus, failing to fully contribute to regional development. In Bahia, cassava production, in comparison to other crops, is precarious, due to technological limitations, lack of public policy-making and the asymmetrical expansion of capitalism that divided producers into two groups: those that employ technology to extract the cassava root, and subsequent bi-products, and those that continue using manual methods. These factors have contributed to the weakening of the value/production chain. The individual producers that remain in rural areas are those that have been excluded from the capitalist system. It was found that cassava production, whilst sustaining the families of these producers, did not encourage rural workers to continue living in rural areas, since the young rural residents have, in general, not chosen to continue the work of the previous generation. In the cooperatives, it was found that, despite restricting the range of products extracted from cassava (usually starch or flour), they were sufficiently organized to meet the needs of producers and take advantage of market opportunities. Cassava production lacks public policy initiatives and technology. Profits are small, as is the quantity of studies in the area. Furthermore, demand has fallen away and there is a lack of investment in the sector that exploits cassava.